1998
DOI: 10.1039/a805420g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of alkyl aromatics using a novel silica supported Schiff base complex

Abstract: A new heterogeneous catalyst based on a chemically modified mesoporous silica gel and possessing immobilised chromium ions has been prepared and successfully applied to the aerial oxidation of alkyl aromatics at atmospheric pressure and in the absence of solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 4 publications
0
59
0
2
Order By: Relevance
“…The modification routes are essentially nucleophilic substitutions (22), formation of Schiff's bases (28), and diazotations (29) and are conditioned mainly by the kind of immobilized organic group. However, it was clearly shown that the efficacy of these subsequent reactions is progressively decreased by access difficulties to some immobilized groups on the silica surface (26).…”
Section: Resultsmentioning
confidence: 99%
“…The modification routes are essentially nucleophilic substitutions (22), formation of Schiff's bases (28), and diazotations (29) and are conditioned mainly by the kind of immobilized organic group. However, it was clearly shown that the efficacy of these subsequent reactions is progressively decreased by access difficulties to some immobilized groups on the silica surface (26).…”
Section: Resultsmentioning
confidence: 99%
“…Desta forma, as propriedades destas sílicas modificadas quimicamente sofreram alterações, que puderam ser exploradas em várias atividades acadêmicas ou tecnológicas. Assim, a sílica organofuncionalizada encontra principalmente aplicações como fase estacionária para cromatografia [18][19][20][21] ou suporte para materiais com propriedades catalíticas [22][23][24][25][26][27][28][29] . Uma destacada utilização consiste no uso da molécula imobilizada como agente sequestrante para metais, que será enfocado aqui.…”
Section: Figura 1 Esquema Dos Tipos De Grupos Silanóis Normalmente Eunclassified
“…Nos últimos anos, porém, com o avanço da técnica de ressonância magnética no estado sólido de vários núcleos, constata-se que os espectros de 13 C e 29 Si proporcionam resultados bastante confiáveis, no que diz respeito às ligações formadas entre o sililante e a superfície. Assim, um grande número de moléculas ancoradas na superfície da sílica gel aumenta sua capacidade de adorver metais .…”
Section: O Uso Do Agente Sequestrante Imobilizadounclassified
“…Nevertheless, recent works have shown that remote photodegradation can occur in molecules anchored in the vicinity of titanium dioxide domains by through-liquid [7,8] and throughair [9,10] diffusion of active oxidized species, and by surface diffusion of hydroxyl radicals up to distances of 40 mm or so.…”
Section: Methodsmentioning
confidence: 99%